2016
DOI: 10.1099/jmm.0.000293
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of ozenoxacin against isolates of propionibacteria and staphylococci from Japanese patients with acne vulgaris

Abstract: Ozenoxacin, a novel non-fluorinated topical quinolone, was assessed for in vitro antimicrobial activity against clinical isolates of propionibacteria and staphylococci according to the broth microdilution method recommended by the Clinical and Laboratory Standards Institute. The isolates used in this study were collected from Japanese patients with acne vulgaris during a period from 2012 to 2013. The MIC 90 s of ozenoxacin against Propionibacterium acnes (n=266), Propionibacterium granulosum (n=10), Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…25 mg/l in study 1 and study 2, respectively, against S. epidermidis; and 0.12 mg/l in both studies 1 and 2 against coagulase-negative staphylococci. The MIC 90 of ozenoxacin against Propionibacterium acnes was ≤0.06 mg/l in the Japanese study [18], but strains of this species were not included in the present study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…25 mg/l in study 1 and study 2, respectively, against S. epidermidis; and 0.12 mg/l in both studies 1 and 2 against coagulase-negative staphylococci. The MIC 90 of ozenoxacin against Propionibacterium acnes was ≤0.06 mg/l in the Japanese study [18], but strains of this species were not included in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…A second Japanese study of the antimicrobial activity of ozenoxacin against isolates from patients with acne vulgaris reported MIC 90 values of ozenoxacin against S. aureus, S. epidermidis and other coagulase-negative staphylococci of ≤0.06, 0.125 and ≤0.06 mg/l, respectively [18]. In comparison, in the present studies, ozenoxacin MIC 90 values were 0.25 and 0.06 mg/l in study 1 and study 2, respectively, against S. aureus; 1 and 0.…”
Section: Discussionmentioning
confidence: 99%
“…Ozenoxacin, which is a new topical antimicrobial agent for the treatment of skin infections, was approved for clinical use in 2015 in Japan. Because little is known about the potency of ozenoxacin, we evaluated the efficacy of ozenoxacin against high‐level levofloxacin‐resistant strains. We found that ozenoxacin exhibited higher potency than the other quinolones against the strains with two substitutions in both GyrA and ParC.…”
Section: Discussionmentioning
confidence: 99%
“…Ozenoxacin produced a superior clinical and microbiological response when compared with placebo [13,14], and had similar efficacy to retapamulin but showed more rapid microbiological clearance than retapamulin [13]. In Japan, ozenoxacin is used for the treatment of acne vulgaris [20,21].…”
Section: Future Perspectivementioning
confidence: 99%